2008
DOI: 10.3354/meps07334
|View full text |Cite
|
Sign up to set email alerts
|

Space size relative to prey width (Sp/Py) influences macrofaunal colonization of artificial structures

Abstract: We tested an index of habitat complexity, Sp/Py (inter-structural space size/prey body width), by deploying artificial structures on a coral reef near Dibba, United Arab Emirates. The structures were polyethylene tube bundles with tube diameters of 3, 12 and 24 mm and a mixed treatment composed of all 3 tube sizes. We counted and identified mobile macrofauna that colonized the interior of the tubes and divided them into 3 body width categories: small (< 3 mm), medium (3-12 mm) and large (>12 mm). Medium and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…More compartmentalized, less strongly connected architecture would in turn increase community persistence and allow the co-existence of a greater number of species (Thébault andFontaine 2010, Stouffer andBascompte 2011). However, some of the previous studies did not observe a significant relationship between space-size heterogeneity and richness (Bartholomew 2002, Kelaher 2003, Bartholomew and Shine 2008. For example, variation in vertical heterogeneity due to different frond lengths of coralline algae did not affect gastropod diversity (Kelaher 2003), and increased heterogeneity in artificial seagrass plots did not result in increased faunal richness independent of faunal abundance (Bartholomew 2002).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…More compartmentalized, less strongly connected architecture would in turn increase community persistence and allow the co-existence of a greater number of species (Thébault andFontaine 2010, Stouffer andBascompte 2011). However, some of the previous studies did not observe a significant relationship between space-size heterogeneity and richness (Bartholomew 2002, Kelaher 2003, Bartholomew and Shine 2008. For example, variation in vertical heterogeneity due to different frond lengths of coralline algae did not affect gastropod diversity (Kelaher 2003), and increased heterogeneity in artificial seagrass plots did not result in increased faunal richness independent of faunal abundance (Bartholomew 2002).…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, species richness may actually decline after the space sizes are no longer biologically meaningful for most organisms. This has been demonstrated in an experiment with reef macrofauna colonization of artificial tube structures of three different sizes (Bartholomew and Shine 2008). Kelaher (2003) demonstrated that greater density of fronds of coralline algae was negatively correlated with gastropod diversity and abundance, and proposed that there may be an upper threshold of complexity, beyond which negative effects of overly high density of structures are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Since we did not measure body size, it is unknown if this was a relevant trait in our experiment. Related to this, suitability of a habitat is scale dependent; a small organism in proportion to the structure it lives on perceives the complexity of a habitat differently compared to a larger organism (Bartholomew and Shine 2008;Warfe et al 2008).…”
Section: Microhabitat Structural Complexitymentioning
confidence: 99%
“…Bartholomew and Shine (2008) measured Sp/Py and examined prey habitat use of small artificial structures. They found that, with one exception, small coral reef-dwelling prey were excluded from spaces smaller than their body widths (Sp/Py less than 1) and that some prey organisms seemed to prefer spaces that closely matched their body widths (Sp/Py slightly greater than 1) compared with spaces that were much wider than their body widths.…”
mentioning
confidence: 99%